2023
DOI: 10.3389/fpubh.2022.1047127
|View full text |Cite
|
Sign up to set email alerts
|

The attitude of Polish consumers toward food irradiation as one of the methods of food preservation

Abstract: BackgroundFood irradiation is one of the methods of food preservation. Unfortunately, despite many opinions from national and international organizations that confirm the safety of the irradiation technique, the irradiated food market is slowly developing, which is particularly noticeable in European countries, including Poland.ObjectivesThe main objective of this study was to determine the attitude of Polish consumers toward irradiated food and to find out whether familiarizing the respondents with educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…Previous studies identified several key factors contribute to the lack of knowledge or misconceptions about food irradiation. There is generally low awareness and familiarity among consumers, many of whom have never heard of the process, leading to significant knowledge gaps ( 11 ). Misconceptions about the safety and nutritional quality of irradiated foods are prevalent, often fueled by incorrect beliefs that such foods are radioactive or nutritionally depleted ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies identified several key factors contribute to the lack of knowledge or misconceptions about food irradiation. There is generally low awareness and familiarity among consumers, many of whom have never heard of the process, leading to significant knowledge gaps ( 11 ). Misconceptions about the safety and nutritional quality of irradiated foods are prevalent, often fueled by incorrect beliefs that such foods are radioactive or nutritionally depleted ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is generally low awareness and familiarity among consumers, many of whom have never heard of the process, leading to significant knowledge gaps ( 11 ). Misconceptions about the safety and nutritional quality of irradiated foods are prevalent, often fueled by incorrect beliefs that such foods are radioactive or nutritionally depleted ( 11 ). Additionally, insufficient or inappropriate labeling hinders informed consumer choices, as many are unaware of consuming irradiated foods due to lack of clear labeling ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teisl et al [29] found the opposite-U.S. consumers had negative attitudes toward food irradiation. When studying Australian consumers, [63] found that attitudes had a direct, positive effect on their intent to accept irradiated foods, and Buczkowska et al [68] found the same thing when studying Polish consumers. Prominent theories of behavior change posit that attitudes directly affect behavior [40] and behavioral intention [60].…”
Section: Attitudementioning
confidence: 92%